China’s international aid to adult education - Jiang Xiaoying (Adult Education Research Conference, 2021)
International aid or foreign aid has contributed significantly to world development since the end of World War II. Education is regarded as an indispensable component of international aid strategies. China was once a recipient of international aid. China has also been committed to assisting other countries consistently in decades. The unique role of China as both the donor and the recipient country attract worldwide interest in understanding China’s international aid strategy and how it differs from that of Western countries. This study employs document analysis based on the existing literature, government reports, and state leaders’ speeches from a historical perspective. The analysis focuses on the development of aid principles and educational aid practice in China. China began to provide international aid in the 1950s. According to the changes in the domestic and international environment, China’s aid can be divided into three stages. In line with it, the characteristics of China’s educational aid practice change at three different stages. The core principles of China’s international aid are equality, mutual respect, non-interference. Rooted in the Chinese traditional saying of “teaching one to fish rather than giving one fish”, China shared its experience with other developing countries through human resources and technical cooperation. Arguably, China’s educational aid mainly targets adult learners from developing countries across formal, non-formal, and informal settings.
Keywords: Educational aid; China; adult learners; human resources development